The Effectiveness of Using a Virtual Laboratory in Distance Learning on the Measurement Materials of the Natural Sciences of Physics for Junior High School Students - Elza Varih Azizah; Asep Bayu Dani Nandiyanto; Tedi Kurniawan; Muhammad Roil Bilad (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose of this study was to analyze the effectiveness of the use of a virtual laboratory on the measurement material of junior high school in physical sciences distance learning. The method used is quantitative. The results showed that the use of a virtual laboratory for distance learning on the measurement material for Natural Science Education in Physics for Junior High School was effective, as evidenced by the increase in the percentage to 54%. It was found that through virtual laboratory media students saw and took direct measurements so that the material presented could be easily understood by students. From the results, distance learning using virtual laboratory media can be one solution in the implementation of learning so that the essence of learning can still be achieved even though learning is carried out remotely.